Bacterial contamination and its Susceptibility in intensive care unit in Thi-qar province / Iraq - Nazar Nasser (University of Thi-Qar Journal of Science, 2019)
To identify the cause and the source of bacterial infection among patients of intensive careunit this study had been conducted in Al-Imam Al-Hussein hospital in Thi-qar province for the periodfrom 1st September to end of December 2011 .A total of 320 swabs and samples were collected from 17 different sites of Intensive Care Unitenvironment and inoculated on a normal cultural media ,then incubated at 37OC for 24 hour . The growthrevealed different bacterial colonies which had been tested for their morphological and biochemicalcharacteristics. Sixty eight of pure isolates were obtained including 24 (35.29%) Gram positive bacterialisolates, 44(64.71%) of Gram negative bacterial isolates, the highest rates (19.11%) of bacterial contaminationhad been found on the walls and the floor . Sensitivity tests for all isolates were done using 25 typesof commonly used antibiotics in Iraq, the results revealed that the genus Enterobacter spp. had a highresistance as a Gram negative bacteria, and Staphylococcus spp. had a high resistance as a Gram positivebacteria to most of the tested antibiotics, MIC tests for 5 types of antibiotics were applied on the mostresistant and the most sensitive isolates which reflect that all isolates have a low rate of MIC againstCiprofloxacin .